Fast acquisition of left and right ventricular function parameters applying cardiovascular magnetic resonance in clinical routine – validation of a 2-shot compressed sensing cine sequence. (31st December 2022) - Gröschel, Jan; Ammann, Clemens; Zange, Leonora; Viezzer, Darian; Forman, Christoph; Schmidt, Michaela; Blaszczyk, Edyta; Schulz-Menger, Jeanette
Abstract: Objectives. To evaluate if cine sequences accelerated by compressed sensing (CS) are feasible in clinical routine and yield equivalent cardiac morphology in less time. Design. We evaluated 155 consecutive patients with various cardiac diseases scanned during our clinical routine. LV and RV short axis (SAX) cine images were acquired by conventional and prototype 2-shot CS sequences on a 1.5 T CMR. The 2-shot prototype captures the entire heart over a period of 3 beats making the acquisition potentially even faster. Both scans were performed with identical slice parameters and positions. We compared LV and RV morphology with Bland-Altmann plots and weighted the results in relation to pre-defined tolerance intervals. Subjective and objective image quality was evaluated using a 4-point score and adapted standardized criteria. Scan times were evaluated for each sequence. Results. In total, no acquisitions were lost due to non-diagnostic image quality in the subjective image score. Objective image quality analysis showed no statistically significant differences. The scan time of the CS cines was significantly shorter ( p < .001) with mean scan times of 178 ± 36 s compared to 313 ± 65 s for the conventional cine. All cardiac function parameters showed excellent correlation ( r 0.978–0.996). Both sequences were considered equivalent for the assessment of LV and RV morphology. Conclusions. The 2-shot CS SAX cines can be used in clinical routine to acquire cardiac morphology in less time compared to the conventional method, with no total loss of acquisitions due to nondiagnostic quality. Trial registration: ISRCTN12344380. Registered 20 November 2020, retrospectively registered.